Show that cosec(2x) + cot(2x) = cot(x)

cosec(2x) + cot(2x)

CONVERT ALL COSEC/COT/SEC FUNCTIONS INTO FUNCTIONS USING SIN/TAN/COS

= 1 / (sin2x) + cos(2x) / sin(2x)

COMBINE THE TWO FRACTIONS INTO ONE

= [1+cos(2x)] / [sin(2x)]

USE COS AND SIN DOUBLE ANGLE FORMULA

a) COS(2X) = 2COS2(X) - 1

b) SIN(2X) = 2SIN(X)COS(X)

= [1+2cos2(x)-1] / [2sin(x)cos(x)]

COLLECT LIKE TERMS

= [2cos2(x)] / [2sin(x)cos(x)]

DIVIDE BY COS(X) ON BOTH BOTTOM AND TOP OF FRACTION

= [cos(x)] / [sin(x)]

USE IDENTITY [SIN(X)] / [COS(X)] = TAN(X)

= [1] / [tan(x)]

USE IDENTITY [1] / [TAN(X)] = COT(X)

= cot(x)

Answered by Divya K. Maths tutor

65386 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Explain how integration via substitution works.


What is the equation of the tangent to the curve y=x^3+3x^2+2 when x=2


Find the equation of the tangent line to the graph of y=2x^4-7x^3+x^2+3x when x=5


Differentiate 5x^2+5y^2-6xy=13 to find dy/dx


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences